Organizational commitment, job satisfaction and intention to leave: A comparative analysis between part-time and full-time faculties - Simo, Pep; Sallan, Jose M; Fernandez, Vicenç (Education Policy Analysis Archives, 2008)
The importance of part-time work has been growing in recent years, due to its significant increase in today's societies, and higher education institutions have not been alien to this trend. The present research tries to study the relationship between organizational commitment and job satisfaction with the intention to leave the institution, comparing part-time and full-time faculty. An empirical research, grounded in the model proposed by Currivan (1999), has been undertaken, with a sample of faculty of ETSEIAT, a college of the Technical University of Catalonia. Results show the existence of the relationships with organizational commitment, job satisfaction and intention to leave predicted in the literature, and significant differences in job satisfaction and organizational commitment between part-time and full-time faculty. The paper ends with some proposals of further research.